Short Operative Duration and Surgical Site Infection Risk in Hip and Knee Arthroplasty Procedures. (22nd September 2015) - Dicks, Kristen V.; Baker, Arthur W.; Durkin, Michael J.; Anderson, Deverick J.; Moehring, Rebekah W.; Chen, Luke F.; Sexton, Daniel J.; Weber, David J.; Lewis, Sarah S.
Abstract : OBJECTIVE: To determine the association (1) between shorter operative duration and surgical site infection (SSI) and (2) between surgeon median operative duration and SSI risk among first-time hip and knee arthroplasties. DESIGN: Retrospective cohort study SETTING: A total of 43 community hospitals located in the southeastern United States. PATIENTS: Adults who developed SSIs according to National Healthcare Safety Network criteria within 365 days of first-time knee or hip arthroplasties performed between January 1, 2008 and December 31, 2012. METHODS: Log-binomial regression models estimated the association (1) between operative duration and SSI outcome and (2) between surgeon median operative duration and SSI outcome. Hip and knee arthroplasties were evaluated in separate models. Each model was adjusted for American Society of Anesthesiology score and patient age. RESULTS: A total of 25, 531 hip arthroplasties and 42, 187 knee arthroplasties were included in the study. The risk of SSI in knee arthroplasties with an operative duration shorter than the 25 th percentile was 0.40 times the risk of SSI in knee arthroplasties with an operative duration between the 25 th and 75 th percentile (risk ratio [RR], 0.40; 95% confidence interval [CI], 0.38–0.56; P <.01). Short operative duration did not demonstrate significant association with SSI for hip arthroplasties (RR, 1.04; 95% CI, 0.79–1.37; P =.36). Knee arthroplasty surgeons with shorter median operative durations had a lower risk of SSI than surgeons with typical median operative durations (RR, 0.52; 95% CI, 0.43–0.64; P <.01). CONCLUSIONS: Short operative durations were not associated with a higher SSI risk for knee or hip arthroplasty procedures in our analysis. Infect. Control Hosp. Epidemiol. 2015;36(12):1431–1436